Hubungan Status Gizi Ibu Hamil dengan Produksi ASI Pasca Melahirkan di Ruang Siti Hajar RSI Sultan Hadlirin Jepara - Ana Sanjaya; Ratna Ratna; Akbar Amin Abdullah (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Background: Pregnant women with poor nutritional status are at risk of experiencing low breast milk production, which in turn can affect the fulfillment of infant nutrition from an early age. Suboptimal breast milk production impacts the growth and development of infants and has the potential to increase the incidence of malnutrition. Based on preliminary data in the Siti Hajar Room of Sultan Hadlirin Islamic Hospital, Jepara, it was found that several postpartum mothers experienced delayed breast milk production with a history of malnutrition. This condition shows the importance of maternal nutritional status during pregnancy as a factor that directly influences lactation. Objective: This study aims to determine the relationship between the nutritional status of pregnant women and postpartum breast milk production in the Siti Hajar Room of Sultan Hadlirin Islamic Hospital, Jepara. Method: The study used a cross-sectional design with a total sampling technique. A total of 30 postpartum mothers were selected as respondents. The independent variable consisted of the nutritional status of pregnant women as measured by Body Mass Index (BMI), Upper Arm Circumference (LILA), and hemoglobin (Hb) levels. The dependent variable was postpartum breast milk production as observed clinically. Data analysis was performed using the Chi-Square test with a significance level of p < 0.05. Results: The results of the study showed a significant relationship between the nutritional status of pregnant women and breast milk production. Statistical tests found that BMI (p = 0.018), LiLA (p = 0.027), and Hb levels (p = 0.006) had a significant association with the adequacy of breast milk production. Conclusion: The nutritional status of pregnant women was proven to be closely related to postpartum breast milk production. Mothers with good nutritional status tend to produce sufficient breast milk production. This finding emphasizes the need for routine nutritional monitoring of pregnant women and nutritional education during pregnancy to support the success of exclusive breastfeeding.